1980
DOI: 10.1037/0021-9010.65.3.364
|View full text |Cite
|
Sign up to set email alerts
|

Job satisfaction in the United States in the 1970s.

Abstract: Job satisfaction among American workers was examined for 1972 through 1978 with a sample (n = 4,709) made up of seven independently drawn annual national surveys. As was true in the previous decade, there were no substantial changes in overall levels of job satisfaction through 1978, and a number of correlates of job satisfaction remained unchanged. Blacks were less job satisfied than whites, there were no sex differences in job satisfaction, and there was a positive association between job satisfaction and ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
62
2
8

Year Published

1981
1981
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(81 citation statements)
references
References 5 publications
(2 reference statements)
9
62
2
8
Order By: Relevance
“…Thus, the people in the older age range of our sample may be those who have survived the early stresses of their job and done well in their career. These findings are also in line with the positive correlations between age and job satisfaction that are commonly reported (see Weaver, 1980). Marital status was significantly related to Emotional Exhaustion, but not to the other burnout subscales.…”
Section: Demographic Datasupporting
confidence: 90%
“…Thus, the people in the older age range of our sample may be those who have survived the early stresses of their job and done well in their career. These findings are also in line with the positive correlations between age and job satisfaction that are commonly reported (see Weaver, 1980). Marital status was significantly related to Emotional Exhaustion, but not to the other burnout subscales.…”
Section: Demographic Datasupporting
confidence: 90%
“…This paper has not attempted to document its literature sources in the way a normal academic paper would. The paper's general conclusions in some cases agree or overlap with those in Andrews (1991), Smith (1979), Shin (1980), Thomas and Hughes (1986), Veenhoven (1991Veenhoven ( , 1993 and Weaver (1980). Although little-read by economists, the pioneering work on the statistical study of well-being includes Andrews and Withey (1976), Andrews and Inglehart (1978), Campbell, Converse and Rodgers (1976), Campbell (1981), Cantril (1965, Diener (1984), and Larsen, Diener and Emmons (1984).…”
Section: Background Notessupporting
confidence: 59%
“…Previous research indicated that AA workers were more satisfied with their job than Caucasian workers (Bartell, 1981;McNelly, 1989;Weaver, 1980). Eighty-seven percent of subjects in this study were satisfied or very satisfied with their job.…”
Section: Facet Job Satisfactionmentioning
confidence: 44%